Hubungan Kepercayaan Diri (Self Confidence) Mahasiswa Dengan Hasil Belajar Pengembangan Kurikulum Menggunakan Sistem Pembelajaran Jarak Jauh (Pjj) - sukri situmeang; Marjuki Al-Jawi (Thawalib: Jurnal Kependidikan Islam, 2021)
This study aims to describe and examine the relationship between student self-confidence and learning outcomes using the distance learning system (PJJ) during the Covid-19 pandemic. The research method used is descriptive with a correlation form. The population in this study were all students of the Islamic Education (KI) STAI Thawalib study program, Jakarta. The sample used was 21 students who took the Curriculum Development course later. Based on the results of the research obtained, it is concluded that there is a relationship between student self-confidence and the distance learning system (PJJ) and the learning outcomes of the Curriculum Development course during the Covid-19 period. The instrument in this study used the form of test questions, description of learning outcomes and the form of non-test questions on the self-confidence scale. The results showed that there was a positive relationship between self-confidence and student learning outcomes, with the influence of self-confidence by 75.7% on student learning outcomes while 24.3 influenced by factors outside of self-confidence.